Pendugaan Kedalaman Lapisan Akuifer Air Tanah Menggunakan Metode Tahanan Jenis Di Desa Kapek, Kecamatan Gunungsari, Lombok Barat - Melinda Dwi Erintina (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Limited surface-water availability during the dry season has increased the dependence of communities in Kapek Village, Gunungsari District, West Lombok Regency, on groundwater resources as their primary water supply. This condition necessitates subsurface investigations to determine the occurrence and depth of aquifer layers. Accordingly, this study aims to estimate groundwater aquifer depths through the application of a one-dimensional electrical resistivity method using Vertical Electrical Sounding (VES) with a Schlumberger electrode configuration. Data acquisition was conducted at two sounding locations with a maximum half-current electrode spacing (AB/2) of 300 m. The field measurements were subsequently processed using one-dimensional inversion techniques to generate vertical resistivity distribution models. Interpretation was carried out by integrating the inversion results with characteristic resistivity ranges of lithological materials, regional geological information, and surface geological observations. The processing results at Sounding Point 1 indicate the presence of a layer with a resistivity value of approximately 31 Ωm, which is interpreted as an aquifer zone occurring at depths between 47 and 127 m below ground surface. At Sounding Point 2, a layer exhibiting a resistivity value of about 10.1 Ωm was identified and interpreted as an aquifer at depths ranging from 48 to 129 m. These variations in resistivity reflect differences in lithological characteristics and degrees of water saturation between the two locations. These findings provide an initial technical basis for determining suitable drilling depths and locations for groundwater wells and for supporting sustainable groundwater resource management in the study area. Furthermore, the results confirm that the one-dimensional resistivity method with a Schlumberger configuration represents an effective and efficient approach for groundwater exploration in regions where hydrogeological data remain limited.